WNT Signaling in Disease - Li Fang Ng; Prameet Kaur; Nawat Bunnag; Jahnavi Suresh; Isabelle Chiao Han Sung; Qian Hui Tan; Jan Gruber; Nicholas S. Tolwinski (Cells, 2019)
Developmental signaling pathways control a vast array of biological processes during embryogenesis and in adult life. The WNT pathway was discovered simultaneously in cancer and development. Recent advances have expanded the role of WNT to a wide range of pathologies in humans. Here, we discuss the WNT pathway and its role in human disease and some of the advances in WNT-related treatments.